Competence perspective on managing internal process - Sanchez, Ron; Heene, Aimé (Advances in applied business strategy ;, 2005)
The competence-based perspective on strategy and management emerged in the 1990s as a new approach to developing strategy and management theory and practice. In the past decade, the focus on organizational competences - and the resources, capabilities, and processes that create competences - has provided a highly productive broad church for theory development, research, and practice in both strategic and general management. Authored by a multidisciplinary group of scholars and practitioners working within the competence perspective, the papers in this volume contribute to developing a better theoretical and practical understanding of internal processes that significantly affect an organization's competences by exploring the dynamic, systemic, cognitive, and holistic aspects of internal processes.The papers present both theoretical developments and empirical research based on a variety of case studies and other research in diverse industrial and geographical contexts. The papers in this volume develop four themes. Part I includes papers that address the key issues of defining and communicating the strategic logic that directs and guides an organization's competence building and leveraging. The papers in Part II investigate the need to develop strategic flexibilities that enable a firm to respond effectively to a range of future environmental uncertainties. Part III includes papers that focus on ways to identify and operationalize an organization's competences - the ultimate source of an organization's ability to compete effectively in its environment. Part IV presents several papers that investigate the systemic interdependencies of an organization's competence building and leveraging activities.